Cooperation a political, economic, and social theory - Harcourt, Bernard E. 1963- (Columbia University Press, 2023)
Liberal democracy is in crisis around the world, unable to address pressing problems such as climate change. There is, however, another path-cooperation. Cooperation does not depend on electoral politics. Instead, it harnesses the longstanding practices and values of cooperatives: democratic participation, equity, solidarity, and respect for others and the environment. From consumer co-ops to credit unions, worker cooperatives to insurance mutuals, nonprofits to mutual aid, countless examples prove that people working together can extend the ideal of participatory democracy into every aspect of their lives.Bernard E. Harcourt develops a transformative theory and practice that builds on worldwide models of successful cooperation. He identifies the most promising forms of cooperative initiatives and then distills their lessons into an integrated framework: Coöperism. This is a political theory grounded on recognition of our interdependence. It is also an economic theory that can ensure equitable distribution of wealth. Finally, it is a social theory that supplies an alternative to punishment by fostering a range of cooperative organizations and projects to offer education, job and skills training, counseling, and therapy.A creative work of normative critical theory, Cooperation provides a positive vision for addressing our most urgent challenges today. Harcourt shows that by drawing on the core values of cooperation and the power of people working together, a new world of cooperation democracy is within our grasp